The effect of entrepreneurial personality traits of undergraduates in the area of education of physical education and sports on the entrepreneurship tendency - Öztaş, Mehmet; Kasımoğlu, Murat; Şirin, Erkan Faruk (Journal of Human Sciences, 2017)
The aim of the study is to identify the existing situation of entrepreneurship, whose importance gradually increases for the last 20 years, among university students taking education in the area of education of physical education and sports; to study whether or not entrepreneurial personality traits (desire to succeed, resolution, practical intelligence, innovativeness, independence, self-confidence) affect entrepreneurship tendency; and to try to identify the degree of this effect. The sample of the study consist of 610 students from the Departments of Physical Education Teaching, Coaching Education, and Sports Management, who receive undergraduate education in Collegeges of Physical Education and Sports in Karamanoğlu Mehmetbey, Niğde, Aksaray, and Erciyes Universities and Faculty of Sport Sciences, Gazi and Selcuk University. In the study, sociodemographic form as well as “Entrepreneurial Personality Traits Inventory” to identify entrepreneurial personality traits, and Entrepreneurship Education Inventory were utilized. As a result of the study, among entrepreneurial personality traits, other than the factors of innovativeness and independence, it revealed that entrepreneurial personality traits had an effect on entrepreneurship education. In addition, it was also identified that there was a positive directional significant relationship between entrepreneurial personality traits and entrepreneur education. As also understood from here, among the other elements (family, belief, culture, etc.) affecting entrepreneurship, entrepreneurial personality traits have an important place in terms of entrepreneurship education.